Redefining Co-Amorphous Solid Dispersions: The Role Of Flavonoids As Functional Carriers - Maruti, Davange Rupali; Sadikali F, Sayyad; Macchindra J, Chavan (Journal of Neonatal Surgery, 2025)
The advancement of co-amorphous solid dispersions (CSDs) is reshaping drug formulation and tackling the difficulties with poorly soluble drugs. The flavonoids are emerging as innovative functional carriers within this realm. Flavonoids stand out as superior carriers in CSDs compared to traditional excipients, due to their natural, eco-friendly, non-toxicity, and better pharmacokinetic profile. They are also known for their antioxidant, anti-inflammatory, and bio-enhancing properties, and offer dual functionality by stabilizing amorphous drug forms and potentially enhancing bioavailability (BA). Thus, this review explores the potential of flavonoids to redefine CSDs, focusing on their role in improving drug stability, solubility, and BA through π-π stacking, hydrogen bonding, and electrostatic interactions. Such interactions between flavonoids and active pharmaceutical ingredients (APIs) contribute to the suppression of drug recrystallization, a key challenge in the long-term stability of amorphous formulations. This article also explains recent cell lines/ animal studies indicate that incorporating flavonoids as carriers in CSDs can enhance therapeutic outcomes, predominantly for poorly soluble drugs. The unique properties of flavonoids open new avenues in CSD design, making them promising candidates for future drug delivery systems.